6 - La transnationalisation des aliments - VERGOPOULOS, Kostas (Africa Development, 1984)
The food crisis being faced by the Third World currently is not the result of a production crisis since production is actually increasing . It is a crisis provoked by the transnationalization of the systems of food produc- tion . Since the beginning of the seventies , two new elements in food systems have become clear: a) a sudden increase of international trade in food products leading to a brutal accentuation of the structural external orienta- tion of the periphery and b) a brutal decline in the foreign exchange receipts of countries of the periphery combined with an increasing need to finance imports . To date , there have been two types of responses: The ultra-liberal policy of total integration into the world food system and the policy of integrating agriculture and food production in particular into the national system (the policy of self-sufficiency). The ultraliberal response is guided by the micro-economic logic of profitability or simply by the ideological logic of integrating oneself into the world system. Transnational Corporations play a decisive role in the elaboration and implementation of the ultra-liberal strategy. The nationalist response consisting of the integration of agriculture and food production in the national system (Mexico , Rumania , Yugoslavia , Congo, Gabon etc...) attempts to realize two objectives simultaneously: improve the balance of payments, reduce budgetary deficits, and through this promote industrialization. In the elaboration of this strategy, Trans- national Corporations play a marginal role. The liberal response accentuates the food crisis: famines, especially as concerns the poorer classes and urban revolts. In reality, the structure of prices in these countries (often estimated to be two or three times higher than the prices ruling on international markets) is beyond the purchasing power of the popular classes. This explains the increasing need for the state to regulate popular consumption by resulting to social engineering. But this however leads to even further problems: systematic intervention by the state to favour the consumers discourages internal production of food and incites producers to concentrate on exports. Up till today, the ultraliberal policy is dominant and there are no evident signs to support the Wassily Leontief thesis according to which by the year 2000, there should be a slowing-down of international trade in food products provoked by the desires of states to promote national food self-sufficiency. With that question, however, the future lies with food self-sufficiency based on the mobilization of the creative energies of the peasantries and not on the transnationalization and promotion of agricultural exports which would lead to dependency on food imports.